Effects of dosed physical loads on hormonal changes and oxygen exchange in athletes - Tambovtseva, R. V.; Nikulina, I. A. (Theory and Practice of Physical Culture, 2020)
Objective of the present study was to identify the dynamics of the substrate and hormonal changes in highly-skilled athletes specializing in middle-distance running and former track athletes.